The Particulars of Applying Odontoprotectors at Different Stages of Therapeutic Process of Periodontal Diseases (A Scoping Review) - Hlazunov, Oleh; Hruzdeva, Alla; Fesenko, Viktor; Korniichuk, Oleksandr; Penskyi, Kostiantyn (International Journal of Statistics in Medical Research, 2022)
Rational use of drugs underlies the development of a treatment strategy. In particular, it is important in dental practice to properly select odontoprotectors for the prevention, treatment and maintenance therapy of periodontal diseases. A methodological approach based on the Arskey & O’Malley’s framework was applied to analyse the state of knowledge and previous studies on the use of odontoprotector drug group at different stages of the therapeutic process of periodontal disease. Of the 6 initial scientific databases, the research was conducted in 3 databases that best met the specified search conditions: Google (Google Scholar); PubMed; Wiley InterScience (The Cochrane Library). The literature was selected for the last 5 years (2016-2021). A total of 492 scientific papers were analysed. It is established that the available scientific information is divided into 4 main areas: the use of herbal remedies and folk remedies; antibiotic therapy in dental practice; prospects for the use of nanotechnology in dentistry; results of experimental researches and review articles on a particular active pharmaceutical ingredient.